Effect of 2000-meter rowing test on parameters of intestinal integrity in elite rowers during competitive phase - observational study - Hanna Dziewiecka; Joanna Ostapiuk–Karolczuk; Anna Kasperska; Justyna Cichoń-Woźniak; Piotr Basta; Anna Skarpańska-Stejnborn (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The epithelial wall leakage has been extensively studied in sports disciplines like running and cycling. However, little is known about gut permeability in other disciplines, like rowing, especially after the regular competition performance distance of 2000 m. Therefore, our study aimed to check gut permeability after the 2000-meter rowing test in the annual training cycle. The phenomenon of epithelial wall leakage has been the subject of investigations within athletic domains such as running and cycling. Nevertheless, there exists an insufficiency of understanding regarding gut permeability in alternative disciplines, such as rowing, particularly following the completion of a standard competitive distance of 2000 m. Hence, the principal objective of our study was to assess gut permeability after the completion of a 2000-meter rowing test. Methods The study was performed at the beginning of a competitive training phase. Eighteen elite rowers of the Polish Rowing Team participated in study after applying the inclusion/exclusion criteria. The participants performed a 2000-meter ergometer test. Blood samples were taken before the test, after exercise, and after 1-hour of restitution. Parameters, such as I-FABP, LPS, LBP, and zonulin, were determined using appropriate biochemical tests. Results There were no changes between pre- and post-exercise values in I-FABP, LBP, LPS, and zonulin. However, the I-FABP changed from 6,49 ± 2,15 to 8,3 ± 2,71 (ng/ml) during the recovery period, and LBP decreased from 2,73 ± 0,77 to 2,035 ± 0,53 (µg/ml) simultaneously. Other parameters have not changed. Conclusion The results of this study showed that intense physical effort performed during the training period is sufficient to negatively affect the gut integrity of rowers.